Faktor-Faktor Penentu Harga Jual Paket Kremasi - Novi Sri Paramita; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2022)
This research aimed at revealing the background of the establishment of the Dharma Kusuma Crematorium and revealing the determinants of the selling price of crematorium packages in the Dharma Kusuma Crematorium. The research method was descriptive qualitative which consisted of teo types of data, namely primary data and secondary data. The method of data collection was carried out using observation techniques, interview techniques and documentation techniques. The results of this research indicated that the establishment of the Dharma Kusuma Crematorium to reduce the costs of the Ngaben ceremony for families who lack funds and have the goal to provide services to the community, the determining factor for the selling price of cremation packages in the Dharma Kusuma Crematorium is calculated from the facilities and infrastructure provided by the crematorium.Keyword: Crematorium, Ngaben, Selling Price